Influence factors on inter-ethnic relations (for example marriages Overseas Koreans) - Ем., Н. Б. (Journal of Oriental Studies, 2016)
This article examines the geographical, historical, socio-cultural and political factors in the choice of marriage partner on the example of inter-ethnic marriages Overseas Koreans.